A measurement of g using Alexander's diving bell - Quiroga, Matías Abel Oscar (2010)
This paper describes a very simple exercise using an inverted test tube pushed straight down into a column of water to determine the free-fall acceleration g. The exercise employs the ideal gas law and only involves the measurement of the displacement of the bottom of the "diving bell" and the water level inside the tube with respect to the water column surface. The experiment is ideal for students in introductory physics courses.